2014
DOI: 10.1007/s00227-014-2587-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecological tracers and at-sea observations document the foraging ecology of southern long-finned pilot whales (Globicephala melas edwardii) in Kerguelen waters

Abstract: The food and feeding ecology of the poorly known southern long-finned pilot whale (Globicephala melas edwardii) was investigated using ecological tracers (muscle and skin δ 13 C and δ 15 N, and total mercury, Hg) on individuals from two mass strandings together with at-sea observations of live animals in Kerguelen waters, southern Indian Ocean. Sightings of cetaceans from long-liners over 9 years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) emphasized the regular occurrence of pilot whales in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 91 publications
2
7
0
Order By: Relevance
“…, Fontaine et al . ). Killer whales have occasionally been observed foraging on cephalopods, for example in western Alaska (Hanson and Walker , J. Durban, P. Wade).…”
Section: Discussionmentioning
confidence: 97%
“…, Fontaine et al . ). Killer whales have occasionally been observed foraging on cephalopods, for example in western Alaska (Hanson and Walker , J. Durban, P. Wade).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, data on Hg concentrations and transfer to food webs, and their spatial and temporal trends, are still very scarce in oceanic waters of the Southern Hemisphere. This is particularly true for the southern Indian Ocean, with no data on temporal variations in seawater Hg patterns, only limited information on Hg distribution and speciation (Cossa et al 2011, Lamborg et al 2014, and some information on bioaccumulation in biota (e.g., Bocher et al 2003, Carravieri et al 2014a, Fontaine et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Sample-size corrected standard ellipse areas (SEA c ; solid lines) and convex hull areas (dotted lines) for killer whales (KIW), sperm whales (SPW) and southern pilot whales (PIW) in Antarctic and subantarctic waters. Individual values of δ 13 C and δ 15 N of skin samples (points) for Crozet (this study), Marion (Reisinger et al 2016), Antarctic Type C (Krahn et al 2008), Ant arctic Type B1 and B2 (Durban et al 2017) killer whales, sperm whales from Crozet/Kerguelen (this study) and southern pilot whales from Kerguelen (Fontaine et al 2015) are shown included king penguins, small sized Patagonian toothfish (TL 43 cm) and the prey item with the lowest δ 13 C value, adult female southern elephant seals (δ 13 C = −21.9 ± 0.7 ‰, n = 70). Group C (δ 15 N = 12.7 ± 0.4 ‰) contained medium sized toothfish (TL 63 cm), elephant seal pups, Ant arctic fur seals and subantarctic fur seals.…”
Section: Diet Reconstructionmentioning
confidence: 89%
“…Sperm whale skin samples were collected from fishing vessels operating in the Crozet and Kerguelen EEZs in January and February 2011, using the same equipment and protocols, and were treated using the same process as for the Crozet killer whale samples. For southern long-finned pilot whales, whose pelagic habitat overlaps with areas where toothfish fisheries operate but were never observed depredating toothfish on longlines, published skin isotopic values from weaned individuals (> 3 m in length) at Kerguelen were used (Fontaine et al 2015).…”
Section: Species and Sample Collectionmentioning
confidence: 99%